Assessing High School Students' Creative Thinking Skills on Green Chemistry Material Using STEM-Based Creative Content Electronic Portfolios - Rahman M. Fiqri; Nahadi; .Siswaningsih W. (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop a valid and reliable STEM-based electronic assessment portfolio instrument to instill creative thinking skills in high school students on the topic of Green Chemistry. This study uses a Design Development Research (DDR) approach with the ADDIE model, which is specifically limited to the development phase. This study involved 16 grade 10 science students. The Assessment Portfolio was designed with three tasks: a summary of the Green Chemistry topic, a poster about the 12 principles of Green Chemistry, and an educational vlog about the principle of "Prevention". The findings indicate that the developed instrument has valid content validity, as assessed by five validators. This instrument was also proven reliable through an inter-rater reliability test conducted by four raters. Furthermore, Wilcoxon test analysis indicates that feedback provided during the electronic portfolio assessment process is effective in significantly improving students' creative thinking skills, with the revision process being the main driver of this improvement. In conclusion, the resulting instrument is effective and can serve as a valid alternative assessment tool.